Browsing the Intangible: Does Visibility Lead to Increased Use?. Issue 2 (3rd April 2018) - Tingle, Natalia; Teeter, Keith
ABSTRACT: Library collections have become fractured as increased acquisition of ebooks has created hybrid print and digital collections. These developments have implications for user awareness of the most current items in the collection and their ability to understand their relationship to print collections, due to ebooks' absence in the physical library space. At the William M. White Business Library at the University of Colorado, Boulder, collocated displays are deployed in the print stacks to promote awareness of ebook collections and enable browsing and serendipitous discovery. This project revealed the difficulty of assessing ebook collections and their promotion when many platforms are involved.